Homeland is remembered with flavors. Patriotic and literary apotheosis of Polish cuisine - Załęczny, Jolanta (Perspektywa stołu, 2023)
People who left their home base after the 19th century uprising, emigrated or sent to Siberia would take with them the most dear memories of people, places, and the tastes they remembered, and they will remind Poland at all times. Later, they described them in their diaries and memoirs, and the writers recorded them on the pages of a novel and in verses of poems. Away from their home country, they tried to recall Polish dishes, sometimes even trying to prepare them, thus creating a substitute for their homeland. Christmas Eve and holy ceremonies were organized in a Polish way. Some recipes entered the canon of Polish literature and inseparably inscribed in the patriotic and literary apotheosis of Polish cuisine, creating the canon of Polish national cuisine. The master here was Adam Mickiewicz, whose descriptions of dishes and tableware recorded in the pages of the national epic entered the history of literature for good, but also built the image of the homeland through the flavors and smells of dishes considered almost national.